2008
DOI: 10.1007/s10964-008-9367-7
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support and Early Adolescents’ Achievement: The Mediational Roles of Motivational Beliefs and Emotions

Abstract: Although a bulk of literature shows that perceived social support (PSS) influences academic achievement, the mechanisms through which this effect operates received little empirical attention. The present study examined the multiple mediational effects of motivational beliefs (competence beliefs and subjective value) and emotions (anxiety and enjoyment) that may account for the empirical link between PSS (from parents, peers and teachers) and mathematics achievement. The participants of the study were 238 grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
153
3
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(199 citation statements)
references
References 42 publications
16
153
3
9
Order By: Relevance
“…According to our results, as a part of emotional engagement, a sense of belonging at school requires experiences of social cohesion, and this is constructed by emotional and informational support from both teachers and peers. Earlier studies have found connections between supportive relationships and motivational outcomes (Wentzel, 1998) and reported that teacher and peer support is positively associated with students' enjoyment and interest at school and their further achievement (Ahmed et al, 2010;Wentzel, 1998). However, in our data, students perceive providing and receiving social support as the key element in their sense of belonging, which in turn makes it a necessity in the construction of the students' emotional engagement with schoolwork.…”
Section: Findings In the Light Of Previous Literature And Pedagogicalcontrasting
confidence: 78%
“…According to our results, as a part of emotional engagement, a sense of belonging at school requires experiences of social cohesion, and this is constructed by emotional and informational support from both teachers and peers. Earlier studies have found connections between supportive relationships and motivational outcomes (Wentzel, 1998) and reported that teacher and peer support is positively associated with students' enjoyment and interest at school and their further achievement (Ahmed et al, 2010;Wentzel, 1998). However, in our data, students perceive providing and receiving social support as the key element in their sense of belonging, which in turn makes it a necessity in the construction of the students' emotional engagement with schoolwork.…”
Section: Findings In the Light Of Previous Literature And Pedagogicalcontrasting
confidence: 78%
“…When students perceive their teachers as supportive, they are more likely to be interested in academic activities and less likely to be anxious (Baumeister & Leary, 1995;Wentzel, 1998;Yildirim, 2012). For instance, a study of Ahmed et al (2010) revealed that perceived teacher support positively predicted students' interest and enjoyment but negatively predicted anxiety in mathematics. Also, the finding that anxiety is a significant negative predictor of learning strategy and achievement in mathematics is robust (e.g., Lapointe, Legault, & Batiste, 2005;Metallidou & Vlachou, 2007).…”
Section: Motivational and Emotional Responsesmentioning
confidence: 99%
“…The option that describe their socially responsible consumption behavior is 'I make an effort to learn about these issues, and I am willing to pay more or sacrifice product quality in order to use these issues in my purchase decisions'. The instrument to measure social support from network (including parents, peers and teachers) has been adopted from the work of Malecki and Demaray, (2002);Fraser et al, (1996); Johnson et al, (1983);and Ahmed et al (2010), which examines the influence of social network in promotion of learning behavior among adolescents. The instrument contains 4 items: "my parents always advise and inspires me to adopt socially responsible consumption behavior, I always get motivation from my friends and peers to practice socially responsible consumption behavior.…”
Section: Instruments and Measuresmentioning
confidence: 99%